Healthy landscapes: Managing agricultural landscapes in socio-ecologically sensitive areas to promote food security, well-being and ecosystem health - Mendonce, Sharon; Borelli, Teresa; Hunter, Danny; Silva, Ajith; Bandara, Thejana; Ratnayake, Sujith S. (2022)
The Healthy Landscapes project aims to improve the nutrition, health and overall well-being of cascade landscape communities in Sri Lanka, while also strengthening the restoration and sustainable management of Village Tank Cascade Systems, for the enhanced provision of ecosystem services and protection of biodiversity.